The impact of large-scale dynamic load modeling on frequency response in the U.S. Eastern Interconnection. (September 2020) - Bennett, Melanie; Liu, Yilu
Highlights: Large-scale dynamic load modeling has never been performed in the Eastern Interconnect. The EI MMWG 2030 model accuracy has been improved via this research. Improved model accuracy will help to increase the reliability of power grid models in future scenarios. Abstract: Dynamic load modeling has been a forefront topic in power systems research for decades. Studies have shown that accurate load models are needed to capture the true behavior of the grid to certain events. However, in the Eastern Interconnection (EI) Multi-regional Modeling Working Group (MMWG) 2030 power grid model, static load models are still commonly used. This paper discusses the process to develop and implement an interconnection-level dynamic load model using the complex load (CLOD) model in PSSE. The model is applied to 25, 000 loads in the EI MMWG case and the frequency response is analyzed and compared between the existing static load model and the dynamic CLOD model. Considering a case study of 4.5 GW loss of generation, the CLOD model introduces larger inter-area oscillations that impact system stability. The parameters developed for the CLOD model have been validated against real frequency measurements captured using the FNET/Grideye system and are found to have higher accuracy than the static load model.